An Assessment of the Risk Associated with the Movement Turkeys to Market Into, Within, and Out of a Control Area During a Highly Pathogenic Avian Influenza Outbreak in the United States - Cardona, Carol; Alexander, Carie; Bergeron, Justin; Bonney, Peter; Culhane, Marie; Goldsmith, Timothy; Halvorson, David; Linskens, Eric; Malladi, Sasidhar; Ssematimba, Amos; Walz, Emily; Weaver, Todd; et al. (University of Minnesota Center for Secure Food Systems, 2018)
In the event of a highly pathogenic avian influenza (HPAI) outbreak in the United States, poultry industry, local, state, and federal authorities will implement a foreign animal disease emergency response. In these circumstances, permit requests to move poultry and poultry products must be supported by risk assessments which demonstrate that the risk of HPAI spread associated with the movement is acceptable. Performing the risk assessments prior to an HPAI outbreak can enhance emergency response and facilitate timely movement permitting decisions during an outbreak. This document assesses the risk that the movement of market-age turkeys to processing (i.e., turkeys to market), during an HPAI outbreak, from a premises located within the Control Area, will result in HPAI virus spread to a virus-free commercial poultry population (e.g., another poultry farm or birds remaining on a multi-age premises). The purpose of this assessment is to provide regulators with an objective and defensible method of assessing the disease risk associated with the movement of live turkeys (for meat) to slaughter.
Keywords: Avian influenza; Continuity of business; HPAI; Market; Outbreak; Risk; Turkey